Description of two final stadium platystictid larvae from Borneo, including that of Drepanosticta ?attala Lieftinck, identified using DNA barcoding (Odonata: Zygoptera: Platystictidae) - Orr, Albert G.; Dow, Rory A. (Zootaxa, 2015)
The final stadium larva of Drepanosticta ?attala Lieftinck, is described and illustrated based on a single male specimen collected at Kuala Belalong Field Studies Centre, Brunei. The larva was identified by matching the mitochondrial marker COI with that of known adult specimens. The larva presented a good match with both D. attala and D. barbatula Lieftinck in this gene, but as adults of only the former species had been collected at the locality, it is presumed more likely to be that species. Another, unidentified platystictid larva, Platystictidae A, collected at the same general locality is also described. The two larvae show significant differences from each other and from D. sundana Krüger, the only other Oriental region member of the family for which larval morphology is known. The three species are also compared with the larvae of the Neotropical genus Palaemnema, which they closely resemble, despite being currently placed in different subfamilies. Based on this known material, Oriental and Neotropical forms differ significantly in details of mandibular morphology, especially the armature of the molar field.